Anthropometric and physiological profiles of elite Iranian junior rowers - Arazi, H.; Faraji, H.; Mohammadi, S. M. (Middle-East Journal of Scientific Research, 2011)
The purpose of the present study was to determine anthropometric and physiological profiles of elite junior male and female Iranian rowers. The anthropometric and physiological profiles of 33 male and 23 female Iranian elite rowers who were invited to the national training camps were measured. The major results were as follows (male and female respectively): body height (181.1±4.9, 170.3±4.1 cm), body weight (80.6±3.9, 70.1±4.4 kg), length of upper extremity (49.4±3.7, 44.3±4.4 cm), length of lower extremity (104.5±4.7, 93.2±5.7 cm), shoulder width (55.85±3.9, 40.1±3.5 cm), elbow width (30.1±3.2, 24.5±2.3 cm), knee width (39.16±2.7, 36.5±2.5 cm), ankle width (27.1±2.5, 23.5±1.8 cm), body fat percent (10.6±3.6, 15.7±3.8), pull up (29.1±14.1, 19.3±9.5 rep), sit-ups (66±8.5, 59±9.7 rep), bench press (99.3±20.2, 64±14 kg), back squat (109.2±30.3, 62.5±5.52 kg) grip force (58.7±6.8, 34.3±8.1 kg), agility [shuttle run test 25 yard (9.9±0.4, 11.4±0.8 sec), aerobic power (50±3.5, 45.9±5 ml kgG1 minG1), anaerobic power (84.3±8.9, 59.3±4.1 rep) and Sargent jump (31.2±3.4, 24.6±5.5 cm). This data provides specific anthropometric and physiological information from elite Iranian rowers that are important to the sport scientific, coaches and these athletes